A tea polyphenol modified zinc powder-based semi-solid slurry negative electrode and a preparation method and application thereof

CN122907572APending Publication Date: 2026-10-13CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611100287.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,由于锌粉比表面积远大于锌箔,添加剂在浆料中随机分散,大量分子被溶剂化水分子包围,难以持续富集于锌粉/电解液界面,仅少量锌粉颗粒表面能吸附到功能分子,无法保证每一颗锌粉均获得均匀的界面修饰

Benefits of technology

(1)本发明创新性地引入羟丙基甲基纤维素(HPMC)作为单层石墨烯导电剂的分散剂。HPMC具有良好的水溶性,在硫酸锌溶液中浓度十分可控。其分子链中含有多个中等极性的氧极性基团,即羟基和醚键。在制浆初期,HPMC可通过搅拌作用均匀吸附于单层石墨烯表面。单层石墨烯具有二维平面网状结构,比表面积大,表面吸附位点丰富,能够与HPMC分子链充分接触,通过氢键和范德华力形成稳定的界面结合,使HPMC均匀铺展于石墨烯片层表面,有效抑制石墨烯片层之间的π-π堆叠团聚和聚沉,并构筑连续稳定的三维复合导电网络。HPMC分子链的柔性骨架在石墨烯片层间形成空间位阻效应,进一步阻止石墨烯的重新团聚,维持其在浆料中的均匀分散状态。与含有强极性官能团的分散剂相比,HPMC不含有酰胺键、羧基、羧基负离子等强极性氧官能团,因此避免了分散剂中羧基等极性基团优先与Zn2+产生螯合配位作用而使离子迁移动力学大幅降低的问题,也避免了分散剂与水分子形成强结合网络导致浆料黏度过高的问题,还避免了强包覆作用阻碍Zn2+在锌颗粒表面传输的问题。从分子层面来看,HPMC分子链中的醚键氧原子含有孤对电子,可通过弱配位作用与单层石墨烯表面的缺陷位点和含氧官能团产生相互作用,但该相互作用强度适中,不会与Zn2+形成强螯合,因此浆料在保持良好分散性的同时维持了较高的离子迁移速率和电化学反应活性,具有更高的浆料黏度调节可控性和更低的极化作用;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907572A_ABST
    Figure CN122907572A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of preparation of water-based zinc ion battery negative electrode, and specifically discloses a tea polyphenol modified zinc powder based semi-solid slurry negative electrode and a preparation method and application thereof. + The local solvation structure promotes uniform deposition; the pi electron system of the aromatic conjugated structure is coupled with the zinc metal electronic state, so that the inter-particle electron transmission efficiency is improved. Meanwhile, hydroxypropyl methyl cellulose is introduced as a single-layer graphene dispersant, which does not contain strong polar functional groups, so as to avoid the reaction with Zn 2+ Strong chelation, maintain high ion migration dynamics. Both of them realize multi-scale optimization of slurry macroscopic dispersion and particle microscopic interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous zinc-ion battery anode preparation technology, and particularly to a tea polyphenol-modified zinc powder-based semi-solid slurry anode, its preparation method, and its application. Background Technology

[0002] As aqueous zinc batteries develop towards high-capacity and large-scale energy storage, traditional zinc foil anodes, due to their limited active area and concentrated interfacial reactions, struggle to meet the application requirements of high-capacity electrodes. In contrast, zinc slurry electrodes, by dispersing high-specific-surface-area zinc particles within a conductive network, can significantly improve the utilization rate of electrode active materials and possess the potential for thick electrode construction and continuous manufacturing. However, while reducing zinc powder particle size and increasing specific surface area improves electrode reactivity, it also exposes new interfacial stability issues. On one hand, the direct contact between a large amount of active zinc powder and the aqueous electrolyte exacerbates corrosion and hydrogen evolution side reactions; on the other hand, the random accumulation of zinc particles in the slurry easily causes uneven local electron / ion transport, causing the deposition process to tend to occur in locally highly active regions, ultimately inducing uneven deposition and structural failure. Therefore, simultaneously controlling the dispersion stability of the zinc slurry and the reactivity of the zinc powder particle surface is crucial for achieving high-performance zinc slurry electrodes.

[0003] Current research on the stability of zinc paste electrodes mainly focuses on introducing polymer binders or dispersants to adjust the rheological properties of the paste. For example, polymers such as polyacrylamide (PAM) and polyvinyl alcohol (PVA) can improve the sedimentation behavior of zinc particles by increasing the paste viscosity and constructing a flexible network structure. However, these polymers typically mainly act on the macroscopic structure control of the paste, lacking effective restriction on the direct contact between the zinc powder surface and water molecules, making it difficult to fundamentally inhibit the corrosion reaction on the zinc powder surface. Furthermore, excessive polymer coating may hinder the growth of Zn. 2+ Transport on the surface of zinc particles reduces electrode reaction kinetics, resulting in very low utilization of the negative electrode material. Therefore, relying solely on slurry rheology adjustment is insufficient to balance electrode stability and interfacial reactivity; further molecular-level interfacial control of the zinc powder surface is still needed.

[0004] Regarding the selection of dispersants, although carboxymethyl cellulose (CMC) has good thickening and dispersing properties, the large number of carboxyl functional groups in its molecular chain easily react with Zn. 2+ Chelation occurs, altering the local coordination environment of zinc ions and reducing Zn. 2+Effective migration ability, in severe cases even leading to the inability to deposit electrolytes properly. Polyacrylamide (PAM) has a high molecular weight and abundant amide groups, which can enhance slurry viscosity and improve the dispersion stability of zinc particles through molecular chain entanglement. However, PAM's strong adsorption and coating capabilities can easily form an excessively thick polymer coating layer on the zinc powder surface, hindering the interfacial contact between zinc powder and electrolyte, and reducing Zn concentration. 2+ Transport and desolvation kinetics on zinc surfaces increase interfacial polarization and limit deposition / stripping reaction rates. Therefore, existing dispersants inherently present a trade-off between rheological regulation and electrochemical kinetics, making it difficult to achieve a balance.

[0005] Regarding zinc powder interface protection, existing technologies include methods that directly add functional additives to the slurry. However, because the specific surface area of ​​zinc powder is much larger than that of zinc foil, the additives are randomly dispersed in the slurry, with a large number of molecules surrounded by solvated water molecules, making it difficult to continuously enrich them at the zinc powder / electrolyte interface. Only a small number of zinc powder particles can adsorb functional molecules onto their surface, failing to guarantee uniform interface modification for every zinc powder particle. Furthermore, direct addition introduces additional solutes, increasing slurry viscosity and affecting its flowability. Additionally, large amounts of additives can cause thickening, resulting in poor economic efficiency.

[0006] Regarding the selection of conductive agents, multi-walled carbon nanotubes (MWCNTs) have a one-dimensional tubular structure with a relatively limited surface contact area. Furthermore, their outer wall structure with a large curvature restricts the effective spreading and uniform bonding of dispersant molecular chains. MWCNTs are prone to inter-tube entanglement, making it difficult for dispersants to achieve uniform coating and spatial control, thus reducing the structural uniformity of the composite system.

[0007] Furthermore, existing interface modification strategies primarily focus on suppressing corrosion and regulating ion deposition, without addressing mechanisms for controlling interfacial electron distribution and improving interparticle electron transport through conjugated structures. Current solutions only achieve limited improvements in cycling performance under low current density and low areal capacity conditions, failing to meet practical application requirements under high current density and high deposition capacity, and electrode utilization remains very low.

[0008] Therefore, the existing technology has the following unresolved technical problems: the contradiction between dispersant selection and ion transport kinetics is difficult to reconcile; the zinc powder interface protection lacks targeting and uniformity; the interface matching between conductive agent and dispersant is insufficient; there is a lack of molecular-level control over the electron transport behavior of zinc powder surface; and the cycling stability is insufficient under high deposition capacity. Summary of the Invention

[0009] In view of the above-mentioned problems, this invention provides a tea polyphenol-modified zinc powder-based semi-solid slurry anode, its preparation method, and its application. This invention utilizes a hot solution of tea polyphenols to pre-soak zinc powder, allowing tea polyphenol molecules to be directionally adsorbed onto the zinc powder particles through coordination of phenolic hydroxyl groups, forming an organic molecular protective layer. Simultaneously, hydroxypropyl methylcellulose is introduced as a dispersant for the monolayer graphene conductive agent, forming stable adsorption with the graphene sheets through ether bonds and hydroxyl groups to inhibit agglomeration. The polyhydroxy structure of tea polyphenol molecules can reduce the free water activity at the zinc powder interface, inhibit hydrogen evolution corrosion, and regulate Zn... 2+ Localized solvation promotes uniform deposition; its aromatic conjugated π-electron system can couple with the electronic states of zinc metal, promoting interfacial electron delocalization and improving interparticle electron transport efficiency. Hydroxypropyl methylcellulose does not contain strongly polar functional groups, avoiding interaction with Zn. 2+ The strong chelating effect maintains high ion migration kinetics. The two work synergistically to achieve multi-scale optimization of the slurry's macroscopic dispersion and particle micro-interface. At 1 mA·cm⁻¹ -2 Current density and 1 mAh·cm -2 At its surface capacity, the symmetrical battery achieves a cycle life of 1950 hours; at 5 mA·cm -2 and 10mAh·cm -2 The circulation time exceeds 700 hours under high deposition capacity.

[0010] To address the above problems, this invention provides a method for preparing a tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode, comprising the following steps: S1. Dissolve tea polyphenols in deionized water to prepare a tea polyphenol solution, immerse zinc powder in the tea polyphenol solution for modification treatment, and then filter, wash and dry to obtain modified zinc powder with a tea polyphenol molecular layer adsorbed on the surface; S2. Disperse monolayer graphene in a soluble zinc salt solution and then ultrasonically disperse it to obtain a conductive agent dispersion. S3. Hydroxypropyl methylcellulose is added to the conductive agent dispersion and then ultrasonically dispersed to obtain a conductive slurry; S4. Add the modified zinc powder to the conductive slurry, and mix evenly to obtain a tea polyphenol modified zinc powder-based semi-solid slurry negative electrode.

[0011] Preferably, the tea polyphenols are catechins as the active ingredient, and the content of the catechins accounts for 60-80 wt.% of the tea polyphenols; the structure of the catechins is shown in Formula 1: ; Formula 1; The concentration of the tea polyphenol solution is 20~80g / L, and the temperature of the modification treatment is 50~70℃, and the time is 0.5~1h.

[0012] Preferably, the concentration of the tea polyphenol aqueous solution is 60 g / L, and the modification treatment temperature is 60°C for 0.5 h.

[0013] Preferably, the soluble zinc salt includes one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, zinc nitrate, and zinc perchlorate, and the concentration of the soluble zinc salt solution is 0.2~3M.

[0014] Preferably, the amount of monolayer graphene added is 2 to 15 wt.% of the total mass of all substances.

[0015] Preferably, the amount of hydroxypropyl methylcellulose added is 2 to 8 wt.% of the total mass of all substances.

[0016] Preferably, the amount of modified zinc powder added is 30-70 wt.% of the total mass of all substances.

[0017] Based on the same inventive concept, the present invention also provides a tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode prepared by any of the above preparation methods.

[0018] Based on the same inventive concept, the present invention also provides an application of a tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode prepared by any of the above preparation methods in an aqueous zinc-ion battery.

[0019] Preferably, the electrolyte of the aqueous zinc-ion battery is a soluble zinc salt aqueous solution, and the separator is glass fiber.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention innovatively introduces hydroxypropyl methylcellulose (HPMC) as a dispersant for the conductive agent in monolayer graphene. HPMC has good water solubility, and its concentration in zinc sulfate solution is highly controllable. Its molecular chain contains multiple moderately polar oxygen groups, namely hydroxyl and ether bonds. In the early stage of pulping, HPMC can be uniformly adsorbed onto the surface of monolayer graphene through stirring. Monolayer graphene has a two-dimensional planar network structure with a large specific surface area and abundant surface adsorption sites, which can fully contact the HPMC molecular chain and form a stable interfacial bond through hydrogen bonds and van der Waals forces, so that HPMC is uniformly spread on the surface of graphene sheets, effectively inhibiting π-π stacking and aggregation between graphene sheets, and constructing a continuous and stable three-dimensional composite conductive network. The flexible skeleton of HPMC molecular chain forms a steric hindrance effect between graphene sheets, further preventing the re-aggregation of graphene and maintaining its uniform dispersion in the slurry. Compared to dispersants containing strongly polar functional groups, HPMC does not contain strongly polar oxygen functional groups such as amide bonds, carboxyl groups, and carboxyl anions. Therefore, it avoids the preferential reaction of polar groups such as carboxyl groups with Zn in dispersants. 2+This avoids the problem of significantly reducing ion migration kinetics due to chelation coordination, and also avoids the problem of excessively high slurry viscosity caused by the formation of a strong binding network between the dispersant and water molecules. Furthermore, it avoids the problem of strong coating hindering Zn. 2+ The issue lies in transport on the surface of zinc particles. From a molecular perspective, the ether-bonded oxygen atoms in the HPMC molecular chain contain lone pairs of electrons, which can interact with defect sites and oxygen-containing functional groups on the surface of monolayer graphene through weak coordination. However, the strength of this interaction is moderate and will not interact with Zn. 2+ It forms strong chelation, so the slurry maintains a high ion migration rate and electrochemical reactivity while maintaining good dispersibility, and has higher controllability of slurry viscosity adjustment and lower polarization. (3) In this invention, tea polyphenols (TP) are selected as the pre-soaking modifier for zinc powder. TP is mainly composed of catechins and is a small molecule organic compound containing both polyhydroxyl and aromatic conjugated structures, exhibiting excellent water solubility. Since zinc powder differs from zinc foil in that it has a larger content, reactivity, and specific surface area, the solubility of TP in solutions containing zinc sulfate is limited. Direct addition makes it difficult to ensure uniform adsorption of TP by each zinc powder particle. This invention employs a hot solution soaking modification method, which allows for better controllability of TP concentration, adsorption time, and temperature, enabling targeted zinc powder adsorption without affecting the fluidity and viscosity of the slurry. The adsorption and interface regulation process of TP molecules on the zinc powder surface is as follows: TP molecules are rich in catechol structures and polyhydroxyl functional groups. Their phenolic hydroxyl groups can interact strongly with the zinc surface through Zn-O coordination, forming a stable organic molecular adsorption layer on the zinc particle surface. This adsorption layer effectively isolates the zinc powder from direct contact with the aqueous electrolyte, reducing the contact area between the zinc powder and water molecules. Meanwhile, the TP adsorption layer restricts the free migration of water molecules through hydrogen bonding, reduces the concentration of highly reactive water molecules in the interfacial region, weakens the possibility of water molecules participating in electron transfer processes, and thus inhibits the water reduction reaction (HER) and the accompanying OH-. - It induces corrosion reactions and reduces the formation of insulating corrosion byproducts such as basic zinc sulfate. The hydroxyl oxygen in the TP molecule has strong polarity and can react with Zn. 2+ Coordination occurs, regulating Zn 2+ Surrounding localized solvation structures, replacing Zn 2+ Some water molecules in the solvent sheath reduce Zn 2+ The strong coordination between Zn and water molecules makes Zn 2+ During deposition, desolvation and electron transfer processes can be completed more uniformly. Compared to the disordered hydration layer on the surface of bare zinc powder, the organic interface layer constructed by TP can reduce local solvation structural fluctuations and alleviate Zn contamination. 2+Uneven flux leads to localized over-deposition, thus promoting uniform nucleation and dense deposition. Furthermore, the aromatic ring conjugated structure in TP molecules possesses an abundant π-electron system. After adsorption onto the zinc powder surface, it can couple with the electronic states of zinc metal, promoting interfacial charge delocalization and redistribution, and reducing electron transport obstacles in the particle contact region. A uniformly adsorbed TP molecular layer improves the interfacial contact between zinc powder particles, reducing electron transport breakpoints caused by oxide layers on particle surfaces or insufficient contact, and constructing a more continuous electron transport network. The phenolic hydroxyl groups in TP enhance the interfacial bonding between the organic molecular layer and the zinc surface through Zn-O coordination, forming a more stable electronic connection interface between zinc powder particles. Therefore, TP modification does not improve conductivity by providing an additional conductive phase, but rather improves the electron transport efficiency between zinc powder particles through interfacial electronic structure regulation and particle contact optimization, thus contributing to uniform Zn²⁺ deposition. + The deposition provides a stable supply of electrons.

[0021] (3) Compared to directly adding TP to the slurry system, TP pre-soaked on the zinc powder surface can achieve interfacial directional distribution of functional molecules. In the direct addition mode, TP molecules are randomly dispersed in the slurry electrolyte environment. A large number of molecules are easily surrounded by solvated water molecules or interact disorderly with HPMC molecules, making it difficult to continuously accumulate at the zinc powder / electrolyte interface, resulting in low utilization of effective active sites. However, through the pre-soaking strategy, TP molecules form a stable coordination with the zinc surface through phenolic hydroxyl groups, constructing a uniform molecular protective layer on the surface of zinc powder particles, which can continuously regulate the interfacial water distribution and Zn 2+ Localized solvation structure. The stable surface adsorption layer avoids random migration and consumption of TP in the slurry, maintaining the interfacial protection effect for a long time. At the same time, the pre-soaking method does not introduce additional solutes into the slurry, does not increase the slurry viscosity, requires less ligand additives, and is more economical.

[0022] (4) In this invention, a stable composite network is formed between HPMC and monolayer graphene. The graphene sheet structure constructs a continuous electron transport channel in the slurry, reducing the contact impedance between zinc particles, allowing more zinc particles to obtain sufficient electron supply and participate in electrochemical reactions. The HPMC molecular chains maintain the uniform dispersion of zinc powder and graphene through steric hindrance, avoiding local deactivation areas caused by particle agglomeration. The TP adsorption layer stabilizes the surface of zinc powder, inhibits corrosion side reactions during storage and cycling, reduces the generation of insulating byproducts, and regulates Zn² + Interfacial solvation structures promote uniform deposition / stripping processes. These two approaches address macroscopic dispersion instability and microscopic interfacial side reactions in zinc paste systems, respectively, achieving multi-scale synergistic optimization from paste structure to particle interfaces. This allows for the reversible utilization of more active zinc powder during recycling, ultimately improving the utilization rate of active materials in the paste electrode. (At 1 mA·cm⁻¹) -2Current density and 1 mAh·cm -2 Symmetrical batteries with the same areal capacity can achieve a cycle life of up to 1950 hours at 5 mA·cm⁻¹. -2 and 10mAh·cm -2 With high deposition capacity, the cycle life exceeded 700 hours, and the zinc powder utilization rate increased from 1% to over 20%. In high deposition capacity symmetric cell tests, the semi-solid slurry electrode using TP adsorption modified zinc powder showed a cycle life nearly 15 times longer than that using ordinary zinc powder. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 The Zn||Zn symmetric cell of Comparative Example 2 of this invention operates at 1 mA·cm -2 Current density and 0.5 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 2 The Zn||Zn symmetric cell of Comparative Example 3 of this invention operates at 1 mA·cm -2 Current density and 0.5 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 3 The Zn||Zn symmetric cell of Comparative Example 1 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 4 The image shows the SEM and elemental mapping of Comparative Example 1 of this invention; where a is the SEM image; b is the Zn elemental distribution map; c is the C elemental distribution map; and d is the O elemental distribution map. Figure 5 The above are SEM and element mapping images from Embodiment 3 of the present invention; wherein, a is the SEM image; b is the Zn element distribution map; c is the C element distribution map; and d is the O element distribution map. Figure 6 The images show the XRD patterns of byproducts from the semi-solid slurry negative electrode in Comparative Examples 1, Examples 1, 2, and 3 of this invention. Figure 7 The Zn||Zn symmetric cell of Comparative Example 4 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 8 The Zn||Zn symmetric cell of Comparative Example 5 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 9 The Zn||Zn symmetric cell of Comparative Example 6 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 10 The Zn||Zn symmetric cell of Comparative Example 7 of this invention is at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 11 The Zn||Zn symmetric cell of Comparative Example 8 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 12 The Zn||Zn symmetric cell of Comparative Example 9 of this invention operates at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 13 Electronic conductivity tests were conducted for Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 of this invention. Figure 14 The Zn||Zn symmetric cell of Embodiment 1 of the present invention is at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 15 The Zn||Zn symmetric cell of Embodiment 2 of the present invention is at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 16 The Zn||Zn symmetric cell of Embodiment 3 of the present invention is at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 17 The Zn||Zn symmetric cell of Example 4 of this invention is at 1 mA·cm -2 Current density and 1 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 18 These are ionic conductivity test graphs for Comparative Example 1, Example 1, Example 2, Example 3, and Example 4 of the present invention; Figure 19 The Zn||Zn symmetric cells of Comparative Example 1 and Example 3 of this invention were tested at 5 mA / cm. -2 Current density and 10 mAh·cm -2 Cyclic test diagram under areal capacity; Figure 20 The graphs show the cycle performance test results of the assembled full cells in Comparative Example 1 and Example 3 of this invention. Detailed Implementation

[0025] To make the present invention easier to understand, specific embodiments are described below to further illustrate the invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical terms used below have the same meaning as understood by those skilled in the art; unless otherwise specified, the raw materials and reagents involved herein can be purchased commercially or prepared by known methods.

[0026] It should be noted that the tea polyphenols used in the embodiments and comparative examples of this application were all purchased from Maclean's, and the content of catechins in the tea polyphenols was 80 wt.%.

[0027] To address the problems mentioned in the background art, this invention provides a tea polyphenol-modified zinc powder-based semi-solid slurry anode, its preparation method, and its application. This invention utilizes a hot tea polyphenol solution to pre-soak zinc powder, allowing tea polyphenol molecules to be directionally adsorbed onto the zinc powder particle surface through coordination of phenolic hydroxyl groups, forming an organic molecular protective layer. Simultaneously, hydroxypropyl methylcellulose is introduced as a dispersant for the monolayer graphene conductive agent, forming stable adsorption with the graphene sheets through ether bonds and hydroxyl groups to inhibit agglomeration. The polyhydroxy structure of tea polyphenol molecules can reduce the free water activity at the zinc powder interface, inhibit hydrogen evolution corrosion, and regulate Zn... 2+ Localized solvation promotes uniform deposition; its aromatic conjugated π-electron system can couple with the electronic states of zinc metal, promoting interfacial electron delocalization and improving interparticle electron transport efficiency. Hydroxypropyl methylcellulose does not contain strongly polar functional groups, avoiding interaction with Zn. 2+ The strong chelating effect maintains high ion migration kinetics. The two work synergistically to achieve multi-scale optimization of the slurry's macroscopic dispersion and particle micro-interface. At 1 mA·cm⁻¹ -2 Current density and 1 mAh·cm -2At its surface capacity, the symmetrical battery achieves a cycle life of 1950 hours; at 5 mA·cm -2 and 10mAh·cm -2 The circulation time exceeds 700 hours under high deposition capacity.

[0028] The following examples and comparative models further illustrate this point.

[0029] Example 1 This embodiment provides a method for preparing a tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode, comprising the following steps: (1) Weigh 2g of tea polyphenols and add them to 0.1L of deionized water. Mix them thoroughly by magnetic stirring to prepare a tea polyphenol solution with a concentration of 20g / L. Heat the solution to 60℃ and add 5g of zinc powder. Soak the solution at 60℃ by magnetic stirring for 0.5h (i.e., zinc powder slurry). Then filter, wash and dry to obtain modified zinc powder (TPZn-20). (2) Add 0.25g of monolayer graphene to 5g of 1M ZnSO4 aqueous solution, stir magnetically and sonicate for 1h to obtain a conductive agent dispersion; (3) Add 0.25g of hydroxypropyl methylcellulose (HPMC) to the conductive agent dispersion and mix thoroughly by magnetic stirring to obtain a conductive slurry; (4) Add 5g of modified zinc powder (TPZn-20) to the conductive slurry and stir magnetically to obtain a semi-solid slurry negative electrode based on tea polyphenol modified zinc powder.

[0030] Example 2 The difference between this embodiment and embodiment 1 is that 2g of tea polyphenols in step (1) is replaced with 4g of tea polyphenols (i.e., the concentration of the tea polyphenol aqueous solution is 40g / L) to obtain modified zinc powder (TPZn-40); other steps and parameters are the same as in embodiment 1.

[0031] Example 3 The difference between this embodiment and embodiment 1 is that 2g of tea polyphenols in step (1) is replaced with 6g of tea polyphenols (i.e., the concentration of the tea polyphenol aqueous solution is 60g / L) to obtain modified zinc powder (TPZn-60); other steps and parameters are the same as in embodiment 1.

[0032] Example 4 The difference between this embodiment and embodiment 1 is that 2g of tea polyphenols in step (1) is replaced with 8g of tea polyphenols (i.e., the concentration of the tea polyphenol aqueous solution is 80g / L) to obtain modified zinc powder (TPZn-80); other steps and parameters are the same as in embodiment 1.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that step (1) is omitted, i.e., ordinary zinc powder without tea polyphenol modification is used; other steps and parameters are the same as in Example 1, and a semi-solid zinc slurry negative electrode is obtained.

[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that step (1) is omitted (i.e., ordinary zinc powder without tea polyphenol modification is used), and the hydroxypropyl methylcellulose (HPMC) in step (3) is replaced with carboxymethyl cellulose (CMC); all other steps and parameters are the same as in Example 1. The specific preparation steps are as follows: (1) Add 0.25g of monolayer graphene to 5g of 1M ZnSO4 aqueous solution, stir magnetically and homogenize by ultrasonication for 1h to obtain a conductive agent dispersion; (2) Add 0.25g of carboxymethyl cellulose (CMC) to the conductive agent dispersion and mix thoroughly by magnetic stirring to obtain a conductive slurry; (3) Add 5g of ordinary zinc powder to the conductive paste and stir with magnetic force to obtain a uniform semi-solid zinc paste negative electrode.

[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that step (1) is omitted (i.e., ordinary zinc powder without tea polyphenol modification is used), and hydroxypropyl methylcellulose (HPMC) in step (3) is replaced with polyacrylamide (PAM); all other steps and parameters are the same as in Example 1. The specific preparation steps are as follows: (1) Add 0.25g of monolayer graphene to 5g of 1M ZnSO4 aqueous solution, stir magnetically and homogenize by ultrasonication for 1h to obtain a conductive agent dispersion; (2) Add 0.25g of polyacrylamide (PAM) to the conductive agent dispersion and mix thoroughly by magnetic stirring to obtain a conductive slurry; (3) Add 5g of ordinary zinc powder to the conductive paste and stir with magnetic force to obtain a uniform semi-solid zinc paste negative electrode.

[0036] Comparative Example 4 The difference between this comparative example and Example 1 is that the tea polyphenols in step (1) are replaced with aniline (AE, solid powder); the other steps and parameters are the same as in Example 1, and modified zinc powder (AEZnP) is obtained and a slurry negative electrode is prepared.

[0037] Comparative Example 5 The difference between this comparative example and Example 1 is that the tea polyphenols in step (1) are replaced with phenol (PO, solid powder); the other steps and parameters are the same as in Example 1, and modified zinc powder (POZnP) is obtained and a slurry negative electrode is prepared.

[0038] Comparative Example 6 The difference between this comparative example and Example 1 is that the tea polyphenols in step (1) are replaced with 1,3-propanediol (PL, liquid); the other steps and parameters are the same as in Example 1, and modified zinc powder (PLZnP) is obtained and a slurry negative electrode is prepared.

[0039] Comparative Example 7 This comparative example provides a method for preparing tea polyphenols by directly adding them to a slurry, comprising the following steps: (1) Add 0.011g of tea polyphenol powder (0.024mmol, which has reached the maximum solubility in zinc sulfate electrolyte) to 5g of 1M ZnSO4 aqueous solution; (2) Add 0.25g of monolayer graphene to the solution in step (1), stir magnetically and homogenize by ultrasonication for 1h to obtain a conductive agent dispersion; (3) Add 0.25g HPMC to the conductive agent dispersion and mix thoroughly by magnetic stirring to obtain conductive slurry.

[0040] (4) Add 5g of ordinary zinc powder to step (3) and obtain a uniform semi-solid zinc slurry negative electrode by magnetic stirring.

[0041] Comparative Example 8 This comparative example provides a method for preparing a solid zinc powder anode, including the following steps: (1) Weigh 0.7g of ordinary zinc powder, 0.2g of single-layer graphene and 0.1g of polyvinylidene fluoride (PVDF) respectively, mix them in N-methylpyrrolidone (NMP) solvent, and grind manually for 0.5 h to obtain a mixed slurry; (2) The mixed slurry in step (1) is coated onto a stainless steel mesh and dried at 80°C for 6 hours to obtain a solid zinc powder negative electrode.

[0042] Comparative Example 9 The difference between this comparative example and comparative example 8 is that ordinary zinc powder is replaced with tea polyphenol modified zinc powder (TPZn-60) prepared in example 3; all other steps and preparation conditions are the same as those in comparative example 8.

[0043] Performance testing and results analysis: The semi-solid / solid zinc powder anodes prepared in Examples 1-4 and Comparative Examples 1-9 were filled into polytetrafluoroethylene molds as zinc anodes. A 1M ZnSO4 solution was used as the electrolyte, and glass fiber was used as the separator. Symmetrical cells were then assembled with the chip anodes. The electrochemical performance was then tested using a Newway battery testing system under the following conditions: current density 1 mA·cm⁻¹. -2 The surface capacity is 1mAh·cm³. -2 The cycle performance results of the symmetric cells are shown in Table 1 below: Table 1:

[0044] Note: The mass percentages in Table 1 are accurate to one decimal place.

[0045] The Zn||Zn symmetric cells prepared in Comparative Examples 1, 2, and 3 were subjected to cycle performance tests, and the results are as follows: Figure 1 , Figure 2 and Figure 3 As shown. By Figure 1 , Figure 2 and Figure 3 It can be seen that all three groups used ordinary zinc powder and had the same components and conditions except for the dispersant. The cycle life of Comparative Example 1 using HPMC was 156 hours, Comparative Example 2 using CMC could not cycle and discharge normally and underwent water electrolysis, and Comparative Example 3 using PAM only cycled for 80 hours. This indicates that the hydroxyl and ether bonds in the HPMC molecular structure have moderate polarity, which can improve the dispersion of zinc particles through hydrogen bonding and steric hindrance, while avoiding the reaction between the carboxyl groups in the CMC molecular chain and Zn. 2+ The decrease in ion migration capacity due to strong chelation coordination and the Zn-dependent strong coating of PAM amide groups. 2 + Interfacial transport and desolvation kinetics are hindered, thus HPMC can achieve a better balance between slurry rheological control and electrochemical kinetics.

[0046] The modified zinc powders prepared in Example 3 and Comparative Example 1 were subjected to SEM morphology observation and elemental mapping analysis, and the results are as follows: Figure 4 and Figure 5 As shown. By Figure 4 and Figure 5 It can be seen that the original zinc powder in Comparative Example 1 has a rough and irregular surface structure and no obvious enrichment of C element was observed. The modified zinc powder in Example 3 has a smoother surface and obvious C element distribution signal, indicating that tea polyphenol molecules were successfully introduced and adsorbed on the surface of zinc powder particles, which has a regulatory effect on the surface state of the particles.

[0047] The semi-solid slurry anodes prepared in Examples 1-4 and Comparative Example 1 were subjected to XRD tests, and the results are as follows: Figure 6 As shown. By Figure 6 It can be seen that after standing, the ordinary zinc powder slurry (semi-solid slurry anode) in Comparative Example 1 showed obvious diffraction peaks of basic zinc sulfate (Zn4SO4(OH)6·xH2O), while no obvious diffraction peaks of basic zinc sulfate were detected in the tea polyphenol modified zinc powder slurry (semi-solid slurry anode) in Examples 1-4. This indicates that the tea polyphenol molecular adsorption layer can effectively inhibit the self-corrosion behavior of zinc powder in the slurry environment. Its polyhydroxy structure reduces the direct contact between zinc powder and water molecules and regulates the local chemical environment of the interface, thereby reducing water-induced side reactions and OH- ions.- This accumulation inhibits the formation of insulating corrosion byproducts such as basic zinc sulfate.

[0048] The Zn||Zn symmetric cells prepared in Examples 1-4 were subjected to cycle performance tests, and the results are as follows: Figure 14-17 As shown. By Figure 16 and Figure 3 The comparison shows that Example 3 has a cycle life of 1950 hours, while Comparative Example 1 only has 156 hours, representing a more than 12-fold increase in cycle life. This indicates that tea polyphenol molecules construct a stable organic molecular adsorption layer on the zinc powder particle surface through the coordination of phenolic hydroxyl groups with Zn-O on the zinc surface. This adsorption layer can effectively reduce the activity of interfacial free water and inhibit hydrogen evolution corrosion. Simultaneously, through the coupling of the π-electron system of the aromatic conjugated structure with the electronic state of zinc metal, it promotes interfacial charge delocalization and improves the electron transport efficiency between zinc powder particles, thereby synergistically optimizing the chemical stability and electrochemical reversibility of the zinc powder surface at the molecular level. Figure 14 , Figure 15 , Figure 16 and Figure 17 The comparison shows that as the concentration of tea polyphenols infusion increases from 20 g / L to 60 g / L, the cycle life of the symmetrical battery gradually increases from 820 h to 1950 h. However, when the concentration is further increased to 80 g / L, the cycle life decreases to 1730 h.

[0049] The slurry negative electrodes prepared in Examples 1-4 and Comparative Example 1 were subjected to electronic conductivity and ionic conductivity tests, and the results are as follows: Figure 13 and Figure 18 As shown. By Figure 13 and Figure 18 It can be seen that as the concentration of tea polyphenols increases from 20 g / L to 60 g / L, the electronic conductivity of the slurry increases. When the concentration increases to 80 g / L, both electronic conductivity and ionic conductivity decrease. This indicates that an appropriate amount of tea polyphenols can effectively protect the zinc powder surface and optimize electron transport through polyhydroxy coordination and aromatic conjugated electronic regulation. However, excessive tea polyphenol molecules will form a thick organic adsorption layer on the zinc powder surface, which will increase interfacial polarization and hinder electron transport, leading to a decrease in deposition / stripping reaction kinetics. Therefore, 60 g / L is the optimal soaking concentration, which achieves a reasonable balance between interfacial stability and reaction kinetics.

[0050] The Zn||Zn symmetric cell prepared in Comparative Example 4 was subjected to cycle performance testing, and the results are as follows: Figure 7 As shown. By Figure 16 (Example 3) and Figure 7The comparison shows that Example 3, which uses tea polyphenols with polyhydroxy and aromatic conjugated structures, has a cycle life of 1950 h, while Comparative Example 4, which uses aniline with amino and aromatic conjugated structures, has a cycle life of only 205 h. This indicates that the oxygen atom in the hydroxyl group has a high electronegativity and can form a more stable adsorption structure with the zinc surface through Zn-O coordination. At the same time, the hydroxyl group can form a hydrogen bond network with interfacial water molecules to reduce the activity of free water. Although the lone pair electrons of the amino group can interact with the metal surface, its strong electron donor characteristics may lead to local electron enrichment, and a single nitrogen coordination site is difficult to form a stable and uniformly covered interfacial adsorption layer.

[0051] The Zn||Zn symmetric cell prepared in Comparative Example 5 was subjected to cycle performance testing, and the results are as follows: Figure 8 As shown. By Figure 16 (Example 3) and Figure 8 The comparison shows that Example 3, which uses tea polyphenols with multi-hydroxyl substitution structures, has a cycle life of 1950 h, while Comparative Example 5, which uses phenol with a single hydroxyl group, has a cycle life of 397 h. This indicates that multiple ortho- and ortho-hydroxyl groups in the tea polyphenol molecule can form multiple coordination interactions with the zinc surface, enhancing molecular adsorption stability and constructing a more dense and uniform organic interface layer. Simultaneously, the multi-hydroxyl structure can provide more Zn. 2+ Interaction sites to promote Zn² + The process involves uniform adsorption and desolvation, while monohydroxyphenol mainly relies on a single oxygen site to interact with the zinc surface, resulting in a limited adsorption layer coverage for Zn. 2+ The ability to regulate the solvation structure and the interfacial water environment is insufficient.

[0052] The Zn||Zn symmetric cell prepared in Comparative Example 6 was subjected to cycle performance testing, and the results are as follows: Figure 9 As shown. By Figure 16 (Example 3) and Figure 9 The comparison shows that Example 3, which uses tea polyphenols containing multiple hydroxyl groups and aromatic conjugated structures, has a cycle life of 1950 h, while Comparative Example 6, which uses 1,3-propanediol containing multiple hydroxyl groups but no aromatic conjugated structures, has a cycle life of only 304 h. This indicates that the aromatic ring conjugated system of tea polyphenol molecules can promote interfacial electron delocalization, optimize electron transport between zinc powder particles, and regulate Zn. 2+ The local charge distribution during the deposition process is affected by the lack of aromatic conjugated structures, making it difficult for molecules to form a continuous and stable molecular protective layer and effectively regulate the electron distribution on the zinc powder surface and the charge transport behavior between particles.

[0053] The Zn||Zn symmetric cell prepared in Comparative Example 7 was subjected to cycle performance testing, and the results are as follows: Figure 10 As shown. By Figure 16 (Example 3) and Figure 10The comparison shows that Example 3, which uses tea polyphenol pre-soaking to modify zinc powder, has a cycle life of 1950h, while Comparative Example 7, which directly adds tea polyphenols to the slurry, has a cycle life of only 498h. This indicates that the pre-soaking strategy enables tea polyphenol molecules to form a stable coordination with the zinc surface through phenolic hydroxyl groups, constructing a uniform molecular protective layer on the surface of zinc powder particles, achieving interfacial directional distribution and continuous stable adsorption of functional molecules. In contrast, with the direct addition method, tea polyphenol molecules are randomly dispersed in the slurry electrolyte environment, with a large number of molecules surrounded by solvated water molecules or interacting disorderly with HPMC molecules, making it difficult to continuously accumulate at the zinc powder / electrolyte interface. The utilization rate of effective active sites is low. At the same time, the direct addition method introduces additional solutes, increasing the viscosity of the slurry and affecting its flowability.

[0054] The Zn||Zn symmetric cells prepared in Comparative Examples 8 and 9 were subjected to cycle performance tests, and the results are as follows: Figure 11 and Figure 12 As shown. By Figure 11 and Figure 12 It can be seen that the solid electrode of Comparative Example 9, which uses tea polyphenol-modified zinc powder, has a cycle life of 128 hours, while the solid electrode of Comparative Example 8, which uses ordinary zinc powder, has a cycle life of only 22 hours. This indicates that the tea polyphenol adsorption layer can inhibit interfacial side reactions and regulate Zn. 2+ Deposition behavior improves the stability of zinc powder electrodes, and the interfacial regulation effect of tea polyphenols is equally effective in solid-state systems.

[0055] The Zn||Zn symmetric cell prepared in Comparative Example 9 was subjected to cycle performance testing, and the results are as follows: Figure 12 As shown. By Figure 16 (Example 3) and Figure 12 The comparison shows that the cycle life of Example 3, which uses tea polyphenol-modified zinc powder to prepare a semi-solid slurry electrode, is 1950 h, while that of Comparative Example 9, which uses the same tea polyphenol-modified zinc powder to prepare a solid electrode, is only 128 h. This indicates that tea polyphenols mainly play an interfacial regulation role, while the dispersed network constructed by HPMC in the slurry system can further optimize the zinc particle distribution and ion / electron transport process. The semi-solid slurry morphology allows the electrode to adaptively adjust the interfacial microstructure through the rheological properties of the slurry during operation. The two work together to give the zinc slurry electrode better electrochemical performance.

[0056] The Zn||Zn symmetric cells prepared in Example 3 and Comparative Example 1 were subjected to an A·cm⁻¹ test at 5 mA·cm⁻¹. -2 Current density and 10 mAh·cm -2 High deposition capacity cycling performance tests were conducted at the areal capacity, and the results are as follows: Figure 19 As shown. By Figure 19It can be seen that the symmetrical battery in Example 3 has been stably cycled for more than 700 hours (and is still cycling), while the battery in Comparative Example 1 could not discharge normally after only 56 hours of stable cycling. This indicates that the electronic conductivity of the slurry was optimized after the introduction of tea polyphenols, the side reactions at the zinc powder interface were effectively suppressed, the composite conductive network constructed by HPMC and monolayer graphene could maintain a continuous electron supply under high current density, the tea polyphenol adsorption layer could stabilize the zinc powder interface and promote uniform deposition, and the two worked together to enable the slurry electrode to maintain excellent cycling stability under high deposition capacity conditions, and the zinc powder utilization rate increased from 1% to more than 20%.

[0057] The full cells prepared in Example 3 and Comparative Example 1 (using NH4V4O) 10 Conductive carbon black and polyvinylidene fluoride were mixed in N-methylpyrrolidone solvent at a mass ratio of 7:2:1, and uniformly coated onto stainless steel foil. After vacuum drying at 80°C for 12 hours, the mixture was cut into NH4V4O. 10 Positive electrode; the semi-solid zinc slurry of Example 3 and Comparative Example 1 were respectively filled into a polytetrafluoroethylene mold as zinc negative electrode, using 1M ZnSO4 aqueous solution as electrolyte and glass fiber as separator, and reacted with the above-mentioned NH4V4O 10 (Positive electrode assembly of the full cell) at 4A·g -1 The following cyclic performance test was conducted, and the results are as follows: Figure 20 As shown. By Figure 20 It can be seen that the initial capacity of the full battery in Example 3 reaches 150 mAh·g. -1 After 500 cycles, the capacity retention rate reached 83%, while the initial capacity of Comparative Example 1 was only 107 mAh·g. -1 Furthermore, the rapid decay indicates that the tea polyphenol-modified slurry electrode not only improves the cycle stability of symmetrical cells, but also exhibits long-term cycle stability in actual full-cell applications, proving the practical value of the modified slurry electrode of this invention.

[0058] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for preparing a semi-solid slurry negative electrode based on tea polyphenol modified zinc powder, characterized in that, Includes the following steps: S1. Dissolve tea polyphenols in deionized water to prepare a tea polyphenol solution, immerse zinc powder in the tea polyphenol solution for modification treatment, and then filter, wash and dry to obtain modified zinc powder with a tea polyphenol molecular layer adsorbed on the surface; S2. Disperse monolayer graphene in a soluble zinc salt solution and then ultrasonically disperse it to obtain a conductive agent dispersion. S3. Hydroxypropyl methylcellulose is added to the conductive agent dispersion and then ultrasonically dispersed to obtain a conductive slurry; S4. Add the modified zinc powder to the conductive slurry, and mix evenly to obtain a tea polyphenol modified zinc powder-based semi-solid slurry negative electrode.

2. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 1, characterized in that, The tea polyphenols contain catechins as active ingredients, and the content of catechins accounts for 60-80 wt.% of the tea polyphenols; the structure of the catechins is shown in Formula 1: ; Formula 1; The concentration of the tea polyphenol solution is 20~80g / L, and the temperature of the modification treatment is 50~70℃, and the time is 0.5~1h.

3. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 2, characterized in that, The concentration of the tea polyphenol solution is 60 g / L, and the modification treatment is performed at a temperature of 60°C for 0.5 h.

4. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 1, characterized in that, The soluble zinc salt includes one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, zinc nitrate, and zinc perchlorate, and the concentration of the soluble zinc salt solution is 0.2~3M.

5. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 1, characterized in that, The amount of monolayer graphene added is 2 to 15 wt. of the total mass of all substances.

6. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 1, characterized in that, The amount of hydroxypropyl methylcellulose added is 2-8 wt.% of the total mass of all substances.

7. The method for preparing the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode according to claim 1, characterized in that, The amount of modified zinc powder added is 30-70 wt. of the total mass of all substances.

8. A semi-solid slurry negative electrode based on zinc powder modified with tea polyphenols, prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the tea polyphenol-modified zinc powder-based semi-solid slurry negative electrode as described in claim 8 in an aqueous zinc-ion battery.

10. The application according to claim 9, characterized in that, The electrolyte in the aqueous zinc-ion battery is a soluble zinc salt aqueous solution, and the separator is made of glass fiber.